Morphometrics and allometry of the larvae of five Characiformes species in the Paraíba do Sul River Basin. Issue 4 (11th July 2017) - Souza, Guilherme; Caramaschi, Erica P.; Monteiro, Leandro R.
Summary: The aim of this study was to analyse the morphology and allometry of larvae belonging to five potamodromous species. Five breeding species belonging to the order Characiformes [ Salminus brasiliensis (Cuvier, 1816), Leporinus steindachneri, Eigenmann, 1907, Prochilodus lineatus (Valenciennes, 1837), Prochilodus vimboides (Kner, 1859) and Brycon insignis, Steindachner, 1877] were used to obtain larvae samples during the pre-flexing, post-flexing, and juvenile developmental stages. When we observed the degree-hour (DH) amplitude time values, we found three developmental groups based on allometry and morphometrics within the period between the pre-flexing and post-flexing phases. Group 1 consists of the species S . brasiliensis and B . insignis, Group 2 consists of P . lineatus and P . vimboides, and Group 3 consists of L . steindachneri . Group 1 requires less development time and has more slender larvae. Group 2 has a moderate development time and larvae with a more rounded shape. Group 3 presents a greater development time and an intermediate larval morphology. It was possible to classify the larvae through cross-validated discriminant analyses based on seven morphometric variables with 90% accuracy in B . insignis, 83% in L. steindachneri, 91% in P . lineatus, 80% in P . vimboides, and 96% in S . brasiliensis . These results indicate larval characteristics that can be used for the taxonomic identification of the icthyoplankton.